BOOK REVIEW: TALES FROM THE PADDY FIELDS: SOUTHEAST ASIAN FOLKTALES ON RICE CULTURE - Dewi, Novita (LLT Journal: A Journal on Language and Language Teaching, 2022)
This is a review of a book titled Tales from the Paddy Fields that covers folktales about paddy in Southesat Asian countries. Picture books delight children and stories from this book can be used as materials in TEYL. Revisiting possible gender bias is needed here if teaching language means transforming the young minds to become not only skillful in language but also culturally and ecologicaly competent.